2012
DOI: 10.1182/blood-2011-02-338210
|View full text |Cite
|
Sign up to set email alerts
|

KIT with D816 mutations cooperates with CBFB-MYH11 for leukemogenesis in mice

Abstract: KIT mutations are the most common secondary mutations in inv (16)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…Recently, mutated KIT was found to cooperate with the CBFB-MYH11 fusion toward leukemogenesis in mice. 38 Our data suggest that this cooperation might be limited to type A fusion transcripts and that other cooperative events occur in inv(16)/t(16;16) AML with non-type A fusions.…”
Section: Cbfb-myh11mentioning
confidence: 61%
See 1 more Smart Citation
“…Recently, mutated KIT was found to cooperate with the CBFB-MYH11 fusion toward leukemogenesis in mice. 38 Our data suggest that this cooperation might be limited to type A fusion transcripts and that other cooperative events occur in inv(16)/t(16;16) AML with non-type A fusions.…”
Section: Cbfb-myh11mentioning
confidence: 61%
“…Recently, mutated KIT was found to cooperate with the CBFB-MYH11 fusion toward leukemogenesis in mice. 38 Our data suggest that this cooperation might be limited to type A fusion transcripts and that other cooperative events occur in inv(16)/t(16;16) AML with non-type A fusions.To gain further biologic insights into the biology of inv(16)/ t(16;16) AML with different fusion types, we performed a microarray analysis to assess differences in the genome-wide gene expression between patients with non-type A and type A fusion transcripts with wild-type KIT. We observed that patients with non-type A fusion showed an up-regulation of genes involved in the activation of caspase activity, cell differentiation and cell cycle control in addition to increased expression of other genes that have been previously linked to myeloid leukemogenesis, including GFI1 or DNMT3B.…”
mentioning
confidence: 61%
“…12,32,33 Thus, inv(16) AML constitutes a paradigm for the model explaining AML leukemogenesis, where second hits causing survival/proliferation advantage (RAS, KIT, or FLT3 mutations) cooperate with a primary hit (CBFB/MYH11 rearrangement) that confers a block in hematopoietic differentiation. 4 This model is supported by animal studies, where the coexpression of Cbfb/MYH11 with mutant KIT 34 or CBFB/MYH11 with FLT3-ITD 35 induced or accelerated the development of leukemia. Although intensive postremission therapy, such as repetitive cycles of higher doses of cytarabine, has substantially improved outcome of patients with inv(16) AML, 15 approximately half of the patients in this cytogenetic AML subgroup are still not cured.…”
Section: Discussionmentioning
confidence: 90%
“…50 Recent mice studies provided further evidence for mutant Kit as a sufficient cooperative event in CBF leukemogenesis. [50][51][52] In addition, one study showed that the Kit D814V A-loop mutant (corresponding to human KIT D816V ) and a distinct KIT exon 8 mutant differ with respect to their transforming abilities. 52 In that study, the coexpression of Runx1-Run1xt1 and Kit D814V resulted in lethal hematopoietic malignancies of short-term latency (2-4 months) in all cases including AML (45%), myeloproliferative neoplasia (35%), and pre-B-acute lymphoblastic leukemia (20%), whereas only half of the mice that coexpressed Runx1-Runx1t1 and the Kit exon 8 mutant developed AML with a latency of 4-5 months within the observation time of 1 year; AML was the only malignant hematological phenotype noticed in these animals.…”
Section: Kitmentioning
confidence: 99%